STUDI ANALISIS SISTEM MONITORING TEMPERATUR RUANG BEARING - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Rising temperatures can lead to bearing the risk of the gas turbine trip. Because of the many possible causes of bearing temperature increases, the temperature monitoring system required bearing space as an indication of a gas leak heat on the room bearing and additional more accurate analysis to determine the cause of the high temperature turbine bearing. The system of monitoring the temperature in the room bearing will monitor continuously, so that any interference was observed immediately handled by appropriate methods and the possibility of operating losses for their trip from the increase in turbine bearings can be avoided.